Contract Management Control and Monitoring System for the Royal Malaysian Navy – Post Survey Validation via Top Management Experts - Abdul Wahid, Al-Shafiq (International Journal of Integrated Engineering, 2018)
The improvement of Naval Ship Operational Availability remains a critical aspect to navies worldwide. Despite sophisticated methodologies and complex In-Service Support Contracts in place to achieve high operational availability, even the most advanced navies are still struggling to strike a balance between availability targets, budget and regulatory restrictions. This situation is also applicable to the Royal Malaysian Navy. A Contract Management Control and Monitoring System (ConCaMS) was developed to target both human and machinery/systems related factors affecting naval availability or so-called Downtime Influence Factors. These factors are identified and prioritized based on their severity. The resulting system is validated via top management experts that concluded in unison the benefits of ConCaMS especially in improving availabe